A Juridical Analysis of the Crime of Child Trafficking Committed by a Minor - Sungkunen Purba; Rahmayanti (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Child trafficking is a criminal offense that violates children's rights and constitutes a serious issue within the juvenile criminal justice system, particularly when a child is not only a victim but also a perpetrator of the crime, as reflected in Decision Number 6/Pid.Sus-Anak/2024/PN Blb. This study formulates three main issues: the factors that lead children to commit the crime of child trafficking, the role and efforts of law enforcement authorities in handling such cases, and the legal policy and judicial considerations in imposing sanctions on child offenders. This research employs a normative juridical method with statutory, conceptual, and case study approaches. Data were obtained from primary legal materials in the form of legislation and court decisions, as well as secondary legal materials including books and scholarly journals, which were analyzed using descriptive qualitative methods. The findings indicate that children’s involvement as perpetrators is influenced by several factors, including economic hardship, family disharmony, weak parental supervision, peer group influence, and the misuse of digital technology as a means of exploitation. In addressing these cases, law enforcement authorities have acted in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System by prioritizing the protection of children's rights, legal assistance, and the principles of restorative justice. Judicial decisions emphasize the best interests of the child by imposing guidance and vocational training sanctions as alternatives to imprisonment. Therefore, the legal policy applied reflects a balance between law enforcement and child protection while emphasizing rehabilitation and the prevention of recidivism.